Patent Protection under Chinese Law - Pinard, Jeanette L.; Chun-cheng, Lian (Columbia Journal of Asian Law, 1987)
When the People’s Republic of China promulgated its Patent Law on March 12, 1984, it announced to other nations its willingness to accept and protect the notion of intellectual property. At the same time, China expressed its hope that a fully developed patent system would enable it to acquire technology from the rest of the world to enhance its modernization efforts. Prior to enacting a patent law, China had taken preliminary steps to protect intellectual property by joining the World Intellectual Property Organization in March, 1983 and by signing the Paris Convention for the Protection of Industrial Property in December, 1984. The Patent Law itself took effect on April 1, 19852 and the first patents were granted at a meeting of the Chinese Patent Bureau on December 28, 1985.3 Although the Patent Bureau had received thousands of applications, it only granted 143 patents at that time.